The Effects of Homeownership on Social Capital - Ryan Aldiansyah Akbar; Djoni Hartono; Adiwan Fahlan Aritenang (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Access to homeownership is becoming increasingly limited due to various factors related to a decline in social capital, including sense of stability, security, and community attachment. This study examined the relationship between homeownership and social capital in Indonesia at the household level while addressing endogeneity and heterogeneity issues. This research used panel data from the IFLS-4 and IFLS-5 surveys, employing a fixed-effect regression model with robust standard error and instrumental variables. The study found that homeownership significantly impacts social capital in Indonesia. Furthermore, the effect of homeownership differs between Java and non-Java households and between urban and rural households. The study also identified other significant influencing factors of social capital, such as household size and monthly income. It is concluded that policies aimed at increasing homeownership may positively impact social capital in Indonesia. This research has provided evidence of the heterogeneity of the effect of homeownership on social capital based on geographical location and household characteristics, suggesting that policymakers should develop policies to meet the specific needs of each group to maximize the positive impact of homeownership on social capital.